2022
DOI: 10.3389/fvets.2022.902355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium Supplementation on the Ion Homeostasis in the Reproductive Organs and Eggs of Laying Hens Fed With the Diet Contaminated With Cadmium, Lead, Mercury, and Chromium

Abstract: The objective of this study was to explore the toxic effects of different heavy metals in combination with their deposition and ion homeostasis in the reproductive organs and eggs of laying hens, as well as the alleviating action of selenized yeast. A total of 160 Lohmann pink-shell laying hens (63-week-old) were randomly allocated into four treatments with 10 replicates of four hens each. The four dietary treatments were the corn-soybean meal basal dietary (control; CON); the CON dietary supplemented with 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The R 2 values of standard curves for the different heavy metals were higher than 0.99. The recovery rates of Cd, Pb, Cr, Hg, and Se were 91.8–98.4%, 93.9–97.4%, 96.9–100.3%, 97.9–103.7%, and 92.9–102.1%, respectively ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The R 2 values of standard curves for the different heavy metals were higher than 0.99. The recovery rates of Cd, Pb, Cr, Hg, and Se were 91.8–98.4%, 93.9–97.4%, 96.9–100.3%, 97.9–103.7%, and 92.9–102.1%, respectively ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to construct the laying hen model of sub-chronic heavy metal intoxication, the addition of 5 mg/kg Cd, 50 mg/kg Pb, 3 mg/kg Hg, and 5 mg/kg Cr approximates the 10-fold of the limits of national standards, were chosen in this study. In addition, our previous research has indicated that the HEM dosages have disturbed the ion balance of reproductive organs of laying hens ( 44 ). Meanwhile, the maximum permitted limits of Se in poultry feed are 0.5 mg/kg, based on the Se content 1.4 mg/kg in basal dietary, 0.4 mg/kg Se from selenized yeast was used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is impossible to eliminate Pb and Cd from food, research is carried out on methods of limiting its absorption by the body. These methods should be easily accessible and uncomplicated [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Foods containing significant amounts of antioxidant components can be used in the daily diet to prevent the dangerous effects of toxic metals on the human body [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%